Management of medically assisted withdrawal from alcohol in acute adult mental health and specialist addictions in-patient services: UK clinical audit findings. Issue 3 (11th May 2023) - Sinclair, Julia; Barnes, Thomas R. E.; Lingford-Hughes, Anne; Drummond, Colin; Loubser, Ignatius; Rendora, Olivia; Paton, Carol
Abstract : Background: Medically assisted alcohol withdrawal (MAAW) is increasingly undertaken on acute adult psychiatric wards. Aims: Comparison of the quality of MAAW between acute adult wards and specialist addictions units in mental health services. Method: Clinical audit conducted by the Prescribing Observatory for Mental Health (POMH). Information on MAAW was collected from clinical records using a bespoke data collection tool. Results: Forty-five National Health Service (NHS) mental health trusts/healthcare organisations submitted data relating to the treatment of 908 patients undergoing MAAW on an acute adult ward or psychiatric intensive care unit (PICU) and 347 admitted to a specialist NHS addictions unit. MAAW had been overseen by an addiction specialist in 33 (4%) of the patients on an acute adult ward/PICU. A comprehensive alcohol history, measurement of breath alcohol, full screening for Wernicke's encephalopathy, use of parenteral thiamine, prescription of medications for relapse prevention (such as acamprosate) and referral for specialist continuing care of alcohol-related problems following discharge were all more commonly documented when care was provided on a specialist unit or when there was specialist addictions management on an acute ward. Conclusions: The findings suggest that the quality of care provided for medically assisted withdrawal from alcohol, including the use of evidence-based interventions, is better when clinicians with specialist addictions training are involved. This has implications for future quality improvement in the provision of MAAW in acute adult mental health settings.